POLA DAN STRATEGI PEMBINAAN MUALLAF DI KAMPUNG MUALLAF KABUPATEN PINRANG SULAWESI SELATAN (STUDI KASUS POLA PEMBINAAN MUALLAF DI DESA MAKULA DAN SALUKATA KELURAHAN BETTENG KECAMATAN LEMBANG PINRANG) - Ar, Saftani Ridwan; Sya’ban, Syandri (Sulesana: Jurnal Wawasan Keislaman, 2021)
Islamic da’wah in South Sulawesi cannot be separated from common obstacles as is the case in Indonesia, such as financial constraints, lack of educated personnel and militancy to preach to remote areas as well as conflicts of interest with other da’wah institutions. This phenomenon does not become the main obstacle for several da’wah institutions in South Sulawesi in carrying out da’wah tasks, especially da’wah to non-muslims and fostering converts to Islam. There is a trend of increasing the number of non-muslims converting to Islam due to several factors, especially due to the da’wah touch from the preachers of Islamic institutions who are specifically targeting non-muslims in the interior of Pinrang Regency. This research is a field research with a case study in the Makula and Salukata Villages, Betteng Village, Lembang Mesakada District, Pinrang Regency, South Sulawesi. This research uses qualitative methods in analyzing this data, in addition to describing, it also conducts a SWOT analysis, namely an analysis of the advantages, disadvantages, opportunities and obstacles to the problem of Islamic da’wah to non-Muslims, especially in the Pinrang Regency area. The purpose of this study is contribute to Islamic institutions in developing their da’wah to non-muslims and reverts. In this study, it was found that the dominant factors causing non-muslims to embrace Islam were due to the process of deep reflection on the search for truth through religious lectures and persuasion from families who had previously embraced Islam and the factor of marriage. The post-Islamic development process was carried out by bringing in preachers from several Islamic organizations to the village to live together in the converts’ village and become Islamic builder in the area, which was coordinated by the Pinrang Religious Affairs Office.